2018
DOI: 10.1111/1365-2664.13180
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the challenges of public data archiving for citizen science biodiversity recording and monitoring schemes

Abstract: Public data archiving (PDA) is widely advocated as a means of achieving open data standards, leading to improved data preservation, increased scientific reproducibility, and transparency, as well as additional data use. Public data archiving was primarily conceived to archive data from short‐term, single‐purpose scientific studies. It is now more widely applied, including to large‐scale citizen science biodiversity recording and monitoring schemes which combine the efforts of volunteers with professional scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…They found that only 12.3% of biodiversity recorders in the Netherlands supported unconditional reuse of their data, while 36.7% were opposed to commercial use of their data. Current limitations to access and reuse of citizen science data are often attributed to the scientists or organisations running citizen science projects, who may face a range of technological, economic and cultural barriers and disincentives to data sharing (Reichman et al 2011;Schmidt et al 2016;Groom et al 2017;Pearce-Higgins et al 2018). However, our UK results and those from the Netherlands suggest that some limitation is in accordance with the wishes and expectations of citizen science participants.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…They found that only 12.3% of biodiversity recorders in the Netherlands supported unconditional reuse of their data, while 36.7% were opposed to commercial use of their data. Current limitations to access and reuse of citizen science data are often attributed to the scientists or organisations running citizen science projects, who may face a range of technological, economic and cultural barriers and disincentives to data sharing (Reichman et al 2011;Schmidt et al 2016;Groom et al 2017;Pearce-Higgins et al 2018). However, our UK results and those from the Netherlands suggest that some limitation is in accordance with the wishes and expectations of citizen science participants.…”
Section: Discussionsupporting
confidence: 59%
“…Progress towards a more open approach in ecology is hindered by technological and cultural barriers, but solutions and incentives have emerged, alongside new obligations for public data archiving from funding organisations and scientific journals (Reichman et al 2011;Michener 2015;Nosek et al 2015;Culina et al 2018a). Nevertheless, concerns remain about open access to ecological data, and while the views of scientists and organisations have been reported (Moles et al 2013;Mills et al 2015;Pearce-Higgins et al 2018;Tulloch et al 2018), the opinions of citizen scientists themselves have been overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these encouraging findings there are also constraints which have to be taken into consideration. Firstly, data quality is a critical issue in citizen science studies and has often been viewed with scepticism in recent years [8,13,[45][46][47]. In addition to challenges common to any experimental approach, such as damage or loss of recording units, implementation by the farmers plays an important role.…”
Section: Citizen Science As a Research Methodology In Horse Husbandrymentioning
confidence: 99%
“…; Pearce‐Higgins et al . ). Typically, citizen‐science programs consist of volunteers or non‐professionals who undergo training in sampling methods and assist in collecting data about phenomena such as species presence, weather, water quality, and environmental pollution (Figure ; Dickinson et al .…”
mentioning
confidence: 97%